Chemical-looping gasification of biomass: Part II. Tar yields and distributions - Tian, Xin; Niu, Pengjie; Ma, Yuexin; Zhao, Haibo (Biomass & bioenergy, 2018)
Tar, as a kind of by-product in biomass gasification processes, can adversely affect the efficiency of biomass utilization. Chemical-looping technology has been proposed as a novel way to reduce the tar yield in biomass treatment. As the second part of a two-part series work, the tar evolution characteristic during the biomass-derived chemical-looping gasification (CLG) process using bimetallic Cu-Fe oxides as oxygen carrier (OC) was investigated. The tar collected from batch fluidized bed experiment with Cu5Fe5 (50 mol.% CuO + 50 mol.% Fe2O3) as OC was first analyzed by Gas Chromatography-Mass Spectrometer (GC-MS) to qualitatively determine the organic compounds contained. It was found that the relative molecular weight of the compounds was mostly concentrated at about 200. Subsequently, the effects of steam to biomass ratio (S/B, in weight), temperature, and oxygen carrier to biomass ratio (O/B, in weight) on tar reforming were investigated. The results indicated that the increase of temperature, S/B and O/B were all favorable for the decomposition and conversion of large molecular compounds in tar into small ones. In addition, quantitative analyses of the tar collected under the optimal conditions with different Cu-Fe mixed metal oxides as OCs were also conducted. It was found that the Cu composition in OC could promote the decomposition of small molecular compounds in tar, while the Fe composition was beneficial to decrease the yield of large molecular compounds in tar. Furthermore, synergistic reactivity of the bimetallic Cu-Fe OC was achieved for tar decomposition during the biomass-derived CLG process. •The molecular mass of the main compounds in tar are concentrated at about 200.•Effects of temperature, S/B, O/B and Cu/Fe ratio on tar yield are discussed.•Cu poses high reforming reactivity on small molecular compounds in tar.•Fe is beneficial to reduce the yield of large molecular compounds in tar.•Bimetallic Cu-Fe oxide demonstrates synergistic effect on tar decomposition.